2016
DOI: 10.1093/mnras/stw2125
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear and extended mid-infrared emission of Seyfert galaxies

Abstract: We present subarcsecond resolution mid-infrared (MIR) images obtained with 8-10 m-class ground-based telescopes of a complete volume-limited (D L <40 Mpc) sample of 24 Seyfert galaxies selected from the Swift/BAT nine month catalog. We use those MIR images to study the nuclear and circumnuclear emission of the galaxies. Using different methods to classify the MIR morphologies on scales of ∼400 pc, we find that the majority of the galaxies (75-83%) are extended or possibly extended and 17-25% are point-like. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 97 publications
4
31
0
Order By: Relevance
“…On the other hand, dust in the central region of AGN reprocesses some fraction of these high-energy photons, which are then re-emitted in the IR. For this reason, the MIR-X-ray correlation has been widely studied for different types of AGN at various MIR wavelengths (∼6 to 25 µm; see García-Bernete et al 2016, and references therein). However, to date there have been no detailed studies across the entire IR spectral range, and in relation to a set of X-ray bands defined from 3 to 80 keV.…”
Section: T H E C O R R E L At I O N S P E C T Ru M T E C H N I Q U E mentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, dust in the central region of AGN reprocesses some fraction of these high-energy photons, which are then re-emitted in the IR. For this reason, the MIR-X-ray correlation has been widely studied for different types of AGN at various MIR wavelengths (∼6 to 25 µm; see García-Bernete et al 2016, and references therein). However, to date there have been no detailed studies across the entire IR spectral range, and in relation to a set of X-ray bands defined from 3 to 80 keV.…”
Section: T H E C O R R E L At I O N S P E C T Ru M T E C H N I Q U E mentioning
confidence: 99%
“…Due to limitations in the library, we cannot expand the spectral decomposition beyond 22 µm. A detailed description of the method is given in Hernán-Caballero et al (2015), which we already tested in García-Bernete et al (2016).…”
Section: A P P E N D I X a : S P E C T R A L D E C O M P O S I T I O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies reported good fits to the nuclear IR SED of nearby AGNs assuming a clumpy distribution of dust surrounding the central engine (e.g., Mason et al 2006Mason et al , 2009Nikutta, Elitzur, & Lacy 2009;Ramos Almeida et al 2009; hereafter RA09; Ramos Almeida et al 2011b; hereafter RA11; Hönig et al 2010;Alonso-Herrero et al 2011;hereafter AH11;Sales et al 2011;Lira et al 2013;Ichikawa et al 2015;García-Bernete et al 2015;Siebenmorgen, Heymann, & Efstathiou 2015;Fuller et al 2016;Audibert et al 2017;García-González et al 2017). Although the torus properties of nearby Seyfert galaxies have been extensively studied in the literature, to date there have been no studies based on an ultra-hard X-ray (14-195 keV) selected sample of these galaxies using high angular resolution IR data.…”
Section: Introductionmentioning
confidence: 99%